Hazard Potential in Southern Pakistan: A Study on the Subsidence and Neotectonics of Karachi and Surrounding Areas - Tirmizi, Osman; Khan, Shuhab D.; Mirzaee, Sara; Fattahi, Heresh (Remote sensing (Basel, Switzerland), 2023)
Coastal communities in deltaic regions worldwide are subject to subsidence through a combination of natural and anthropogenic processes. The city of Karachi in southern Pakistan is situated along the diffuse western boundary of the tectonically active Indian Plate, making it more susceptible to natural subsidence processes from plate motion-related deformational events such as earthquakes and faulting. Karachi has a dense population of over 16 million people, and determining the rate of subsidence and extent of neotectonic activity is crucial for mitigating seismic hazards. Excessive abstraction of groundwater and extensive groundwater use in irrigation are some of the anthropogenic contributions to subsidence in the area. A combination of the lack of historical data and few previous studies of the area make it difficult to determine the rate and extent of deformation in this region. We present an analysis of subsidence and neotectonic activity in Karachi and its surrounding areas using Interferometric Synthetic Aperture Radar (InSAR) timeseries techniques. The InSAR results for satellite LOS velocity change in both ascending and descending Sentinel-1 tracks indicate subsidence in key residential and industrial areas. Further decomposition into two dimensions (east–west and vertical) quantifies subsidence in these areas up to 1.7 cm per year. Furthermore, InSAR data suggest the presence of an active north–east dipping listric normal fault in North Karachi that is confirmed in the shallow subsurface by a 2D seismic line. Subsidence is known to cause the reactivation of faults, which increases the risk of damage to infrastructure.